A doxycycline- and light-inducible Cre recombinase mouse model for optogenetic genome editing - Vizoso, Miguel; E. J. Pritchard, Colin; Bombardelli, Lorenzo; van den Broek, Bram; Krimpenfort, Paul; Beijersbergen, Roderick L.; Jalink, Kees; van Rheenen, Jacco (Nature communications, 2022)
The experimental need to engineer the genome both in time and space, has led to the development of several photoactivatable Cre recombinase systems. However, the combination of inefficient and non-intentional background recombination has prevented thus far the wide application of these systems in biological and biomedical research. Here, we engineer an optimized photoactivatable Cre recombinase system that we refer to as doxycycline- and light-inducible Cre recombinase (DiLiCre). Following extensive characterization in cancer cell and organoid systems, we generate a DiLiCre mouse line, and illustrated the biological applicability of DiLiCre for light-induced mutagenesis in vivo and positional cell-tracing by intravital microscopy. These experiments illustrate how newly formed HrasV12 mutant cells follow an unnatural movement towards the interfollicular dermis. Together, we develop an efficient photoactivatable Cre recombinase mouse model and illustrate how this model is a powerful genome-editing tool for biological and biomedical research. Achieving spatial control of gene expression is important. Here the authors report an optimised photoactivatable Cre recombinase system, doxycycline- and light-inducible Cre recombinase (DiLiCre), and generate a DiLiCre mouse line which they use for mutagenesis in vivo and positional cell-tracing.